Ghosts and the Japanese: cultural experience in Japanese death legends - Iwasaka, Michiko, author; Toelken, Barre, author; Utah State University Press, publisher (Colorado State University. Libraries, 1994)
The Japanese have ambivalent attitudes toward death, deeply rooted in pre-Buddhist traditions. In this scholarly but accessible work, authors Iwasaka and Toelken show that everyday beliefs and customs--particularly death traditions--offer special insight into the living culture of Japan.
Foreword / David Hufford -- Part I: An introduction to the left stairway -- Part II: Death customs in contemporary Japan -- Suggested reading and related resources -- Part III: Japanese death legends and vernacular culture -- Mothers and children -- Revenge and anger -- Omens -- Ghosts at sea -- Passions -- Epilogue -- Sources and notes -- Suggested reading.
Keywords: Folklore -- Japan; Death -- Japan -- Folklore; Death -- Social aspects -- Japan; Legends -- Japan -- History and criticism; Funeral rites and ceremonies -- Japan; Japan -- Social life and customs